KRONECKER’S LEMMA AND A CONVERSE WITH APPLICATIONS - et al., G SUDHAAMSH MOHAN REDDY (International Journal of Advanced Science and Technology, 2019)
Kronecker’s Lemma asserts that the mean of a real sequence an is zero if converges. We give a new proof for the case an ≥ 0. If an is bounded, a partial converse was given by Hlawka et al [5]. We state sevaral applications of this converse from our work.